Sustainable Waste Management melalui Eco-Entrepreneurship: Pelatihan untuk Mengubah Sampah Menjadi Berkah - Barokah, Rifqa Gusmida Syahrun; Mulyani, Eva Astuti; Alpusari, Mahmud; Anggriani, Mitha Dwi; Guslinda, Guslinda; Hermita, Neni; Munjiantun , Munjiantun (PELITA NUSA TENGGARA, 2025)
Household waste management in Pekanbaru, particularly plastic waste, remains a critical challenge with environmental and economic implications. This community service program aimed to empower housewives through eco-entrepreneurship training based on the 3R principles (Reduce, Reuse, Recycle). The program adopted a Participatory Action Research approach, integrating educational, persuasive, and participatory methods. The results revealed significant improvements in recycling behavior and the production of five types of marketable decorative products, including recycled mirrors and wooden racks. In addition to fostering environmental awareness, the program also created new household-level economic opportunities. These findings demonstrate that empowering communities through environmentally-based entrepreneurship can support behavior change and contribute to the achievement of Sustainable Development Goals, particularly SDG 5 and SDG 12.